Epidemiological study of patients with diabetic foot - Guerra, Fernando Viamont; Lee, Thomas Yi Teh; Eagers, Edward Patrick Sinibaldi; Marcucci Chakkour, Marcelo; Marchi Neto, Noé de; Bergamasco, Jordanna Maria Pereira; Costa, Marco Túlio (Journal of the Foot & Ankle, 2024)
Objective: Describe the epidemiological profile of patients with diabetic foot registered and followed in an orthopedic outpatient clinic. Methods: A retrospective study was conducted, analyzing the medical records of 500 patients. The reason for the initial consultation, age, smoking, alcoholism, body mass index, sex, type of diabetes, and need and type of surgery were analyzed. Results: The reason for the initial consultation was foot ulcer in 198 patients (39.6%), followed by infection in 122 (24.4%). One hundred and twenty patients (24%) had Charcot arthropathy and 60 (12%) diabetic neuropathy. Most patients were male (67.2%), and the mean age was 65 years, with almost 70% over 50 years in initial care. The mean body mass index was 26.11. Most patients reported being non-smokers (81.4%) and non-alcoholics (85.2%). Type II diabetes predominated (94.4%). Amputations were performed in 306 patients (81.4%) at some point during outpatient follow-up, being classified as minor in 182 patients (59.5%) and major in 124 (40.5%). Conclusion: Most patients at the diabetic foot outpatient clinic are men aged over 50 years, non-smokers and non-alcoholics, and with a slightly high body mass index of 26.1. They have already attended the outpatient clinic with foot complications and suffered some level of foot amputation. Level of Evidence IV; Therapeutic Studies; Case Series.